2007
DOI: 10.1108/17465640710749090
|View full text |Cite
|
Sign up to set email alerts
|

Post‐acquisition integration: ways of sensemaking in a management team meeting

Abstract: Purpose -The aim of this paper is to investigate actors' ways of sensemaking through the use of rhetorical strategies, frames, and categories, in a management team meeting. Design/methodology/approach -The empirical data were generated from a video recorded and transcribed management meeting, and participant observation. The analysis of institutional discourses and practices builds upon the assumption that language and texts are the main tools for understanding actors' social reality. The managers' ways of sen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…With regard to qualitative research, Welch and Piekkari (2017) highlight the importance of carefully selected data, which are typically limited in number, because the strength of a qualitative study is in its capacity for depth of insight. Similarly, it is essential for qualitative video analysis to be selective with data to provide in-depth analysis with a clearly defined focus (Hatani, 2015; Rovio-Johansson, 2007) because a broad coverage of samples and a number of associated topics could rather desensitise us to subtle differences of particular issues (Collins et al , 2006). Thus, in the second round of searches, all news videos were perused and selected by focusing on complete video clips that provided adequate expressions about TICAD-V for content analysis, and news that explicitly portrayed key issues relating to TICAD-V and/or Japan’s foreign aid for Africa.…”
Section: Methodsmentioning
confidence: 99%
“…With regard to qualitative research, Welch and Piekkari (2017) highlight the importance of carefully selected data, which are typically limited in number, because the strength of a qualitative study is in its capacity for depth of insight. Similarly, it is essential for qualitative video analysis to be selective with data to provide in-depth analysis with a clearly defined focus (Hatani, 2015; Rovio-Johansson, 2007) because a broad coverage of samples and a number of associated topics could rather desensitise us to subtle differences of particular issues (Collins et al , 2006). Thus, in the second round of searches, all news videos were perused and selected by focusing on complete video clips that provided adequate expressions about TICAD-V for content analysis, and news that explicitly portrayed key issues relating to TICAD-V and/or Japan’s foreign aid for Africa.…”
Section: Methodsmentioning
confidence: 99%
“…Research in the social sciences has shown that people use accounts of their lived experiences as "windows into their life-worlds", when they interpret, explain or activate existing accounts (Schutz, 1970;Scott and Lyman, 1968;Van Manen, 1990;Wittgenstein, 1953Wittgenstein, /1997. From these accounts, researchers make sense of their discursive constructions of reality Experiences of practice-based learning (Liff and Rovio-Johansson, 2015;Rovio-Johansson, 2007). In the study, the goal was to make sense of the designers' practice-based learning in the Workshop.…”
Section: Credibility Of the Datamentioning
confidence: 99%
“…Thus, for an understanding of institutional discourse and institutional practices, the researcher needs to study social encounters in situ in order to acquire knowledge "from within" (Shotter, 1993(Shotter, , p. 19, 2006 and to see how a problem is framed and understood. Therefore, this study is the "study of work" that explains how work is accomplished in the TC meeting (Psathas, 1995;Rovio-Johansson, 2007;Shotter, 2006;Linell, 2009) through an analysis of the members' use of rhetorical strategies, frames and categories.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…The analytic focus is talk-in-interaction, in situ, (Garfinkel, 1967;Schutz, 1967) and the "study of work" that explains how work is accomplished in specific settings (Psathas, 1995;Rovio-Johansson, 2007;Linell, 2009). The study adopts the discursive pragmatism approach proposed by Alvesson and Kärreman (2000).…”
Section: Analysis Of Datamentioning
confidence: 99%